المرتكزات المعرفية لفينومينولوجا متكاملة للتشكيل الاجتماعي للواقع - طويـل, فتيحة (Sciences humaines; Vol. 37 (2014): SCIENCES HUMAINES(Novembre), 2016)
يسعى هذا البحث إلى الكشف         عن المرتكزات المعرفية، التي يمكن استثمارها في إعطاء نموذج متكامل؛ يتجاوز بعض نقاط الضعف              في الأطروحات الفينومينولوجية القائمة على بناءات الخبرة والوعي، وعلى مفاهيم نظرية التشكيل الاجتماعي للواقع ؛ التي تعمل على تحويل المعاني الذاتية لحقائق واقعية موضوعية ضمن محاولة مقدمة لإستدماج مقولات مستوى التحليل بعيد المدى كمفاهيم القوة، وما يمكن أن تحدثه من أثر في سياقات المعنى ؛ وما تلعبه   من دور في تشكيل الخبرة المعاشة لفئات اجتماعية عريضة في واقع الحياة اليومية، مما يعطي للنظرية الفينومينولوجية القدرة على تفسير متكامل لجميع جوانب الظاهرة الاجتماعية، وفق ما تطرحه السوسيولوجيا متعددة الأبعاد.   This research seeks to reveal the platform of knowledge, which can be invested in giving a complete model, that overpass some of the weaknesses in the phenomenology theses based on experience and awareness structure, and on the concepts of the Social Formation Of Reality theory; that works to transform the uniteral meanings into a realistic and objective facts, within a fore attempt to integrate sayings of farreaching analysis level as concepts of power, and what an impress can it make in the contexts of meaning; what role it plays in shaping the lived experience for a wide social catergories in daily life, which gives the phenomenology theory the ability for a complete explanation to all aspects of the social phenomenon, according to what the multidimensional sociology poses.